Strengthening Cultural Identityas Resistance Against Digital Era Hegemony In Madrasah Curriculum Construction - Rustan Efendy; Nurul Al Ihram (Seutia Hukamaa Cendekia, 2025)
The digital era has fundamentally transformed the paradigm of Islamic education, creating serious challenges for the preservation of local cultural identity in the madrasah education system. This study analyzes strategies for strengthening cultural identity as a form of resistance to digital hegemony in the construction of the madrasah curriculum. Using a qualitative design with a comparative case study approach at MAN 1 and MAN 2, Parepare, this study explores how madrasahs integrate local cultural values with the demands of educational digitization. Data were collected through in- depth interviews, participatory observation, and document analysis. The results show that madrasahs face structural challenges in including inconsistent curriculum changes, technological gaps across generations, and regulatory limitations that hinder the integration of local culture. Madrasahs respond to these challenges through strategies of spiritual habituation, the use of the Pancasila Student Profile Strengthening Program, the development of culture-based extracurricular activities, and the implementation of balanced technology control. The findings show that integrating local culture, such as the value of